UJI AKTIVITAS IMUNOSTIMULATOR FRAKSI ETIL ASETAT EKSTRAK ETANOL KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) TERHADAP PROLIFERASI SEL LIMFOSIT MENCIT GALUR SWISS SECARA IN VITRO BESERTA IDENTIFIKASI KANDUNGAN SENYAWA KIMIANYA - Nirmalasari Nirmalasari; Maria Ulfah; Ediati Sasmito (Universitas Wahid Hasyim Semarang, 2013)
ABSTRACTImmunostimulatory agent has an important role in the treatment of infectious disease caused by pathogen. Roselle calyx (Hibiscus sabdariffa L.) used by community as a health drink to enhance body’s immune system. The aims of this research was to know immunostimulatory activity of ethyl acetate fraction of ethanolic extract of roselle calyx on lymphocyte cell proliferation swiss strain mice and to identified the chemical compounds of the fraction. Roselle calyx was extracted by maceration method using ethanol 96% as a solvent. The ethanolic extract was partitioned gradually by n-hexan and ethyl acetate. Series of ethyl acetate fraction were made to concentration 10, 20, 50, 100, 200, 400 μg/mL and positive control PHA 10 μg/mL for tested to lymphocyte cell culture. Immunostimulatory activity test was done according to MTT Assay method. Lymphocyte proliferation activity was analyzed statistically to the value of Optical Density (OD) result of the Enzyme Linked Immunosorbent Assay (ELISA) reader using Kruskal Wallis Test continued by Mann Whitney Test (p<0,05). Identification of the contents phenolic compounds and flavonoids performed by Thin Layer Chromatography (TLC). The result of the research showed that ethyl acetate fraction had lymphocyte cell proliferation activity at the concentration of 50, 100, 200, and 400 μg/mL. The ethyl acetate fraction of roselle calyx contained phenolic compounds and flavonoids. Key words : roselle calyx, ethyl acetate fraction, MTT Assay, immunostimulatory